Assessment of quality of life of spouses of young male catheterized patients - Pramanik, Sandip; Paul, Uttam Kumar; Pal, Dilip Kumar (International Surgery Journal, 2018)
Background: It is needless to mention that, per-urethral or supra-pubic catheter compromises the Quality of Life (QoL) of young male patients. But present study is about the QoL of spouses of those patients and we compared their status of QoL after removal of catheter of patients with catheterized status. Methods: Authors used three tools named World Health Organization Quality of Life scale (WHOQOL BREF), Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI) for this purpose. Results: Authors found statistically significant improvements in all domains of QoL as measured by WHOQOL BREF, improvement in depression and anxiety status as well, measured by Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI) respectively. Conclusions: Present study concluded with the notion to reiterate the fact that the health of spouse has also to be considered about and to be restored into normal state if found abnormal.